Determinants of Crowdfunder Intention on Using The Crowdfunding-Waqf Model: A Case Study of Kitabisa.Com Applications - Anggun Adilah Maharani; Tika Widiastuti (Jurnal Ekonomi Syariah Teori dan Terapan, 2023)
ABSTRACT   This study aimed to analyze the influence of variable factors in the UTAUT2 (Unified Theory of Acceptance and Use of Technology) model on behavioral intention to use CWM (Crowdfunding-Waqf Model) in the Kitabisa.com application. The population used in this study were active users of the Kitabisa.com application, which are spread throughout Indonesia. Data collection techniques in this study used survey techniques by distributing questionnaires online to 174 respondents. The sampling technique used in this study was purposive sampling, which is a sampling technique with certain criteria. This study used the SEM-PLS analysis technique. The results of this study indicate that the Effort Expectancy (EE) and Habit (HB) variables have a significant positive effect on behavioral intention to use CWM (Crowdfunding-Waqf Model) in the Kitabisa.com application, thus wakif really considers the ease of use of  technology and habits as a determining factor in the adoption of a technology, while 5 other variables, namely Performance Expectancy (PE), Price Value (PV), Social Influence (SI), Hedonic Motivation (HM), and Facilitating Condition (FC) variables have no significant positive effect on behavioral intention to use CWM (Crowdfunding-Waqf Model). The reason of these 5 variables are not significant is because the test results from the Hypothesis Test showed a number that was greater than the significance level of 5% or 0.05. Thus, the dependent variable in the form of Behavioral Intention to Use is only influenced by the Effort Expectancy (EE) and Habit (HB) variables. The contribution of this research is to encourage the policy makers to make policies or laws and regulations that can optimize the benefits of developing the waqf crowdfunding model (CWM) and protect all processes related to the use of productive waqf assets whose funds are collected from the Kitabisa.com application. Keywords: Crowdfunding Waqf Model, Kitabisa.com Application, Unified Theory of Acceptance and Use of Technology, Productive Waqf ABSTRAK Peneltian ini bertujuan untuk menganalisis pengaruh faktor variabel di dalam model UTAUT2 (Unified Theory of Acceptance and Use of Technology) terhadap behvioral intention to use CWM (Crowdfunding-Waqf Model) pada aplikasi Kitabisa.com. Populasi yang digunakan dalam penelitian ini adalah pengguna aktif aplikasi KitaBisa.com yang tersebar di seluruh Indonesia. Teknik pengumpulan data pada penelitian ini menggunakan Teknik survey dengan membagikan kuesioner secara online kepada 174 responden. Jenis pengambilan sampel yang digunakan Purposive sampling yaitu teknik penentuan sampel dengan kriteria tertentu. Penelitian ini menggunakan Teknik analisis SEM-PLS. Hasil penelitian ini menunjukkan bahwa variabel Effort Expectancy (EE) dan variabel Habit (HB) berpengaruh positif signifikan terhadap behvioral intention to use CWM (Crowdfunding-Waqf Model) dalam aplikasi Kitabisa.com, dengan demikian wakif sangat mempertimbangkan kemudahan dalam penggunaan suatu teknologi dan kebiasaan merupakan faktor penentu dalam adopsi suatu teknologi, sementara 5 variabel lainnya yaitu variabel Performace Expectancy (PE), Price Value (PV), Social Influence (SI), Hedonic Motivation (HM), dan variabel Facilitating Condition (FC) tidak berpengaruh positif signifikan terhadap behvioral intention to use CWM (Crowdfunding-Waqf Model). Adapun alasan 5 variabel tersebut tidak signifikan adalah karena hasil pengujian dari Uji Hipotesis menunjukkan angka yang lebih besardari tingkat signifikansi 5% atau 0.05. Dengan demikian, variabel dependen berupa Behavioral Intention to Use hanya dipengaruhi oleh variabel Effort Expectancy (EE) dan variabel Habit (HB) di dalam penelitian ini. Kontribusi dari adanya penelitian ini bagi para policy maker adalah dapat membuat kebijakan atau peraturan perundang-undangan yang dapat mengoptimalkan manfaat dari pengembangan Crowdfunding wakaf model (CWM) dan melindungi segala proses terkait pemanfaatan asset-aset wakaf produktif dan dana yang dikumpulkan dari aplikasi Kitabisa.com. Kata Kunci: Crowdfunding Wakaf Model, Aplikasi Kitabisa.com, Unified Theory of Acceptance and Use of Technology, Wakaf Produktif REFERENCES Alalwan, A. A. (2020). Mobile food ordering apps: An empirical study of the factors affecting customer e-satisfaction and continued intention to reuse. International Journal of Information Management, 50, 28–44. doi:10.1016/j.ijinfomgt.2019.04.008 Alalwan, A. A., Baabdullah, A. M., Rana, N. P., Tamilmani, K., & Dwivedi, Y. K. (2018). Examining adoption of mobile internet in Saudi Arabia: Extending TAM with perceived enjoyment, innovativeness and trust. Technology in Society, 55, 100–110. doi:10.1016/j.techsoc.2018.06.007 Darmansyah, Fianto, B. A., Hendratmi, A., & Aziz, P. F. (2020). Factors determining behavioral intentions to use Islamic financial technology: Three competing models. Journal of Islamic Marketing, 12(4), 794–812. doi:10.1108/JIMA-12-2019-0252 Hair, J. F., Hult, G. T. M., Ringle, C. M., Sarstedt, M., & Thiele, K. O. (2017). Mirror, mirror on the wall: A comparative evaluation of composite-based structural equation modeling methods. Journal of the Academy of Marketing Science, 45(5), 616–632.doi:10.1007/s11747-017-0517-x Hapsari, M. I., Bin Mohd Thas Thaker, M. A., Mohammed, M. O., & Duasa, J. (2022). A qualitative investigation into crowdfunding framework as a source of financing for waqf land development. Journal of Islamic Accounting and Business Research, 13(3), 425–443. doi:10.1108/JIABR-10-2020-0311 Henseler, J., Ringle, C. M., & Sinkovics, R. R. (2009). The use of partial least squares path modeling in international marketing. Advances in International Marketing, 20, 277–319. doi:10.1108/S1474-7979(2009)0000020014 Hong, S. J., Thong, J. Y. L., & Tam, K. Y. (2006). Understanding continued information technology usage behavior: A comparison of three models in the context of mobile internet. Decision Support Systems, 42(3), 1819–1834. doi:10.1016/j.dss.2006.03.009 Hsu, C. L., & Lin, J. C. C. (2015). What drives purchase intention for paid mobile apps?-An expectation confirmation model with perceived value. Electronic Commerce Research and Applications, 14(1), 46–57. doi:10.1016/j.elerap.2014.11.003 Kazemi, H., Miller, D., Mohan, A., Griffith, Z., Jin, Y., Kwiatkowski, J., Tran, L., & Crawford, M. (2015). 350mW G-band medium power amplifier fabricated through a new method of 3D-copper additive manufacturing. Proceeding of 2015 IEEE MTT-S International Microwave Symposium, IMS 2015, 36(1), 157–178. doi:10.1109/MWSYM.2015.7167037 Lee, Y. Y., Dato Haji Yahya, M. H., Habibullah, M. S., & Mohd Ashhari, Z. (2020). Non-performing loans in European Union: country governance dimensions. Journal of Financial Economic Policy, 12(2), 209–226. doi:10.1108/JFEP-01-2019-0027 Martins, M., Farias, J. S., Albuquerque, P. H. M., & Pereira, D. S. (2018). Adoption of technology for reading purposes: A study articles of e-books acceptance. Brazilian Business Review, 15(6), 568–588. doi:10.15728/bbr.2018.15.6.4 Mohd Thas Thaker, H., Mohd Thas Thaker, M. A., Khaliq, A., Allah Pitchay, A., & Iqbal Hussain, H. (2022). Behavioural intention and adoption of internet banking among clients' of Islamic banks in Malaysia: an analysis using UTAUT2. Journal of Islamic Marketing, 13(5), 1171–1197. doi:10.1108/JIMA-11-2019-0228 Mohd Thas Thaker, M. A., Mohd Thas Thaker, H., & Allah Pitchay, A. (2018). Modeling crowdfunders' behavioral intention to adopt the crowdfunding-waqf model (CWM) in Malaysia: The theory of the technology acceptance model. International Journal of Islamic and Middle Eastern Finance and Management, 11(2), 231–249. doi:10.1108/IMEFM-06-2017-0157 Sánchez Torres, J. A., & Arroyo-Cañada, F.-J. (2016). Diferencias de la adopción del comercio electrónico entre países. Suma de Negocios, 7(16), 141–150. doi:10.1016/j.sumneg.2016.02.008 Shahzad, K., Zhang, Q., Ashfaq, M., & Hafeez, M. (2022). The acceptance and continued use of blockchain technology in supply chain management"¯: A unified model from supply chain professional's stance. International Journal of Emerging Markets. doi:10.1108/IJOEM-11-2021-1714 Sukmana, R. (2022). Determinant factor of crowdfunders ' behavior in using crowdfunding waqf model in Indonesia"¯: Two competing models. Journal of Islamic Marketing, 14(7), 1793-1816. doi:10.1108/JIMA-08-2021-0246 Tamilmani, K., Rana, N. P., Prakasam, N., & Dwivedi, Y. K. (2019). The battle of Brain vs. Heart: A literature review and meta-analysis of "hedonic motivation” use in UTAUT2. International Journal of Information Management, 46, 222–235. doi:10.1016/j.ijinfomgt.2019.01.008 Venkatesh; Viaswanath, & Davis; Fred D. (2000). A Theoretical Extension of the Technology Acceptance Model: Four Longitudinal Field Studies. Management Science, 46(2), 186–204. Wamba, S. F., & Queiroz, M. M. (2019). The role of social influence in blockchain adoption: The Brazilian supply chain case. IFAC-PapersOnLine, 52(13), 1715–1720. doi:10.1016/j.ifacol.2019.11.448 Wang, E. S. T., & Chou, N. P. Y. (2014). Consumer characteristics, social influence, and system factors on online group-buying repurchasing intention. Journal of Electronic Commerce Research, 5(2), 119–132. Wijaya, F. M. (2023). Evaluasi Mobile Banking Adoption Intention di BCA dan Variabel-Variabel yang Mendukung Use Behavior. BALANCE: Economic, Business, Management and Accounting Journal, 20(1), 86-100. doi:10.30651/blc.v20i1.16381 Zhou, T., Lu, Y., & Wang, B. (2010). Integrating TTF and UTAUT to explain mobile banking user adoption. Computers in Human Behavior, 26(4), 760–767. doi:10.1016/j.chb.2010.01.013